Analysis of Learning Using Web Technologies in Organizing the Independent Works of Engineering Students (Eurasian Research Bulletin, 2023)
This article presents a quantitative analysis of the use of web-based resources to support independent learning among engineering students. The study provides evidence that web technologies can effectively enhance student understanding of course material and improve academic performance. The results suggest that educators should consider incorporating web-based resources into their teaching practices to support self-directed learning among students. Offers valuable insights into the potential benefits of using web technologies to facilitate independent learning in the engineering education context.